2023
DOI: 10.1021/acs.est.3c00771
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling High-Molecular-Weight DBP Toxicity Drivers in Chlorinated and Chloraminated Drinking Water: Effect-Directed Analysis of Molecular Weight Fractions

Abstract: As disinfection byproducts (DBPs) are ubiquitous sources of chemical exposure in disinfected drinking water, identifying unknown DBPs, especially unknown drivers of toxicity, is one of the major challenges in the safe supply of drinking water. While >700 low-molecular-weight DBPs have been identified, the molecular composition of high-molecular-weight DBPs remains poorly understood. Moreover, due to the absence of chemical standards for most DBPs, it is difficult to assess toxicity contributions for new DBPs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…In practical water treatment, source water typically undergoes preprocessing, including coagulation and sedimentation, which can remove a substantial portion of high-molecular-weight DOM precursors before disinfection, , which are believed to be associated with higher degree of oxygenation and unsaturation. , This could explain the differences in the molecular properties between previously reported DBP and the organochlorine compounds observed in this study, as we used the original DOM without pretreatment. Additionally, a recent study employing 21 T FT-ICR MS demonstrated the presence of 509 DBP containing three chlorine atoms in chlorinated or chloraminated drinking water, adding support to the similarity between anthropogenic DBP and natural organochlorine compounds produced through enzymatic chlorination of DOM.…”
Section: Results and Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In practical water treatment, source water typically undergoes preprocessing, including coagulation and sedimentation, which can remove a substantial portion of high-molecular-weight DOM precursors before disinfection, , which are believed to be associated with higher degree of oxygenation and unsaturation. , This could explain the differences in the molecular properties between previously reported DBP and the organochlorine compounds observed in this study, as we used the original DOM without pretreatment. Additionally, a recent study employing 21 T FT-ICR MS demonstrated the presence of 509 DBP containing three chlorine atoms in chlorinated or chloraminated drinking water, adding support to the similarity between anthropogenic DBP and natural organochlorine compounds produced through enzymatic chlorination of DOM.…”
Section: Results and Discussionmentioning
confidence: 86%
“…Statistical analysis showed that these compounds with more chlorine atoms were associated with a greater extent of oxidation and a lower degree of unsaturation, as indicated by the increase of the O/C wa and NOSC wa values and decrease of the DBE wa values with the number of chlorine atoms (Figure S4). This trend indicated the oxidation of DOM molecular structures along with the greater extent of chlorination in both enzymatic and abiotic reactions, which can potentially lead to the formation of low-molecular-weight halogenated aliphatic DBP. , Previous studies have identified that high-molecular-weight halogenated DBP, especially the aromatic fraction, exhibited higher developmental toxicity. ,, Therefore, the difference in the relative abundance of organochlorine compounds generated by different chlorination reactions may suggest their variations in environmental concentrations and associated risks.…”
Section: Results and Discussionmentioning
confidence: 96%
“…In the past two decades, identifying transformation products induced by chemical oxidation has been an active area of research, fueled by development of sensitive high resolution mass spectrometry and protocols for the evaluation of detected features in nontarget analysis. , Considering that more than 350 000 chemicals are currently in commercial production and use, selective screening the universe of chemicals is vital to prioritize toxicologically important chemicals and transformation products for experimental investigations as shown in the ongoing efforts to link DBPs with the toxicity. , With limited commercial availabilities of authentic standards for transformation products, a theoretical approach is critical to tentatively predict reaction products. Toward predicting oxidative transformation products, this perspective article emphasizes the key progress made in experimental measurement of kinetics and transformation products, and theoretical determination of rate constants and elucidation of reaction mechanisms.…”
Section: Background and Significance Of Transformation Products Forma...mentioning
confidence: 99%
“…FT-ICR analysis of halogenated DBPs has been performed by multiple groups in recent years and 15 N-labeling has been previously used to investigate known chloramination DBPs. , To our knowledge, this work is the first to combine the two approaches and include isotopic labeling for untargeted FT-ICR MS analysis of mixtures containing halogens.…”
Section: Introductionmentioning
confidence: 99%